Scientific models versus social reality. Issue 3 (2nd April 2016) - Cartwright, Nancy
Abstract : Policy predictions fail for the very many different kinds of case-by-case local factors described in the Building Research & Information (2015) special issue (vol. 43/4) entitled 'Closing the Policy Gaps: From Formulation to Outcomes'. Work in philosophy of science shows that beyond the case by case, general systematic problems loom that make the gap between theory and practice hard to close. What is needed in response, it is argued here, are ways to cope with the gap and to build an expectation about it into planning predictions, into planning decisions, into the methods of implementing and monitoring, as well as into fallback and failsafe plans. Tracking implementation and outcomes is not only useful for post hoc evaluation but also a powerful tool for getting the intended outcomes in the first place and making the necessary adjustments.